The role of peer support in coping and adjustment to dialysis and transplantation: Study protocol. - Anna Winterbottom; Eleri Wood; Andrew Mooney; Keith Bucknall; Hilary L Bekker (PLoS ONE)
Introduction People with kidney failure receiving dialysis or kidney transplantation find it difficult to adapt to treatment related routines and restrictions, and feel frustrated when their expectations aren't matched by their lived experience. Health professionals provide information to help people prepare for kidney treatments, but it may be that 'peer supporters' - people who live with kidney disease - can provide more easily understood and relevant information. This study will explore how learning from peer supporters might improve the experience of treatment, after dialysis initiation and post-transplantation, by helping them to better understand what to expect from treatments. Methods Two mixed methods studies including in-depth interviews and questionnaires. In each study, participants will be recruited at two timepoints, before commencing dialysis or transplantation, and 6 months later. Questionnaires and interviews will explore expectations and the lived experience of treatment, and if peer support impacts on adjustment and coping with treatment. Participants will be recruited from two large teaching hospitals in the North and South of England, where one has access to a formal kidney peer support program. Discussion Delivering peer support in kidney units is increasingly popular, yet provision is inconsistent and generally low quality. Providing an evidence base for it's use will help guide the optimal development of peer support programmes and efficient allocation of peer resources. A report will be produced to summarise the our findings, which will help kidney units better help people with kidney failure prepare for kidney treatments.